The Influence of Business Resilience, Entrepreneurial Characteristics and Business Experience on Business Sustainability with Education Level as a Moderating Variable in Business Groups in Palangka Raya City - Rexy Hasudungan Biondhy Antang; Irawan Irawan; Lelo Sintani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of business resilience, entrepreneurial characteristics, and business experience on business sustainability, as well as to test the role of education level as a moderating variable. The sampling technique in this study uses an explanatory quantitative approach and a descriptive qualitative technique.Purposive Samplingconducted through Observation and Questionnaires. The sample size taken was 70 samples consisting of respondents who are business actors in the culinary, furniture, and batik sectors in Palangka Raya City. The data analysis technique used Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS 3.2.9 software analysis tool. The results of this study indicate that business resilience, entrepreneurial characteristics, and business experience partially have a positive and significant influence on business sustainability. Business experience was found to be the most dominant factor in determining business existence.